2009
DOI: 10.1002/aic.12056
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the decomposition of 2‐butanol on carbon‐based acid catalyst

Abstract: in Wiley InterScience (www.interscience.wiley.com).The catalytic conversion of 2-butanol on a carbon-based acid catalyst prepared by chemical activation of olive stone with phosphoric acid was investigated. The carbon catalyst showed a considerable amount of surface phosphorus, presumably in form of phosphate groups, as revealed by XPS, despite a washing step carried out after the activation process. Conversion of 2-butanol yields mainly dehydration products, mostly cis-2-butene and trans-2-butene with lower a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…Activated carbons are amorphous carbon materials, mainly characterized by a well-developed porous texture [1]. They are widely used in many different applications including (1) adsorption, both in gas and liquid phases [2][3][4], (2) catalysis, mostly as supports of the active phases [5][6][7][8][9] but also as bulk catalysts [10][11][12][13], and (3) in electrochemical or energy storage applications for use as supercapacitors [14][15][16][17][18]. There is currently a reborn interest in research of the synthesis, characterization, and applications of activated carbons, as shown by recent reviews and the high number of publications on this topic that can be found in the technical literature [19][20][21][22][23][24].…”
Section: Activated Carbonsmentioning
confidence: 99%
“…Activated carbons are amorphous carbon materials, mainly characterized by a well-developed porous texture [1]. They are widely used in many different applications including (1) adsorption, both in gas and liquid phases [2][3][4], (2) catalysis, mostly as supports of the active phases [5][6][7][8][9] but also as bulk catalysts [10][11][12][13], and (3) in electrochemical or energy storage applications for use as supercapacitors [14][15][16][17][18]. There is currently a reborn interest in research of the synthesis, characterization, and applications of activated carbons, as shown by recent reviews and the high number of publications on this topic that can be found in the technical literature [19][20][21][22][23][24].…”
Section: Activated Carbonsmentioning
confidence: 99%
“…Recently, Beltrame et al [211] analyzed the preparation of activated carbon fibers by H 3 PO 4 -activation of pineapple plant leaves for the adsorption of caffeine. The activated fiber showed a surface area of 1031 m 2 •g −1 with a high amount of acid surface groups from the H 3 PO 4 activation process [223,224]. The highest caffeine adsorption capacities were obtained at pH values up to 7, decreasing significantly at pH values of 8 and 9.…”
Section: Contaminantmentioning
confidence: 98%
“…The XPS P2p peak was located at binding energy (BE) around 133 eV and could be fitted to assign the contribution of two peaks one at 132.8 eV and another at 133.6 eV. These contributions to the P2p zone can be described as P groups directly bonded to a carbon site (CPO3 or C2PO2 group), or with a bridge O atom (COPO3 or (CO)3PO groups) [33,34].…”
Section: Synthesis and Characterization Of The Catalystmentioning
confidence: 99%